India - District Poverty Initiatives Project : Joint Interim Assessment - Understanding Differences in Project Design - World Bank (Washington, DC, 2014)
Since 2000, the World Bank has been engaged in community driven development projects called District Poverty Initiatives Projects in four States: Andhra Pradesh, Madhya Pradesh, Chhattisgarh and Rajasthan. These projects are built on the principle of improving rural livelihoods as well as fostering community empowerment. These projects give particular emphasis to the empowerment of communities and groups, with a special focus on women and other excluded segments of the community. The objective of this Joint Interim Assessment is to take stock of what has been learned from the projects, with an eye towards improving the design and implementation of future projects of this type, a number of which are already in the pipeline.